Serological profiling reveals hsa-miR-451a as a possible biomarker of anaphylaxis - Wojciech Francuzik; Kristijan Pažur; Magdalena Dalke; Sabine Dölle-Bierke; Magda Babina; Margitta Worm (JCI Insight, 2022)
Background There is a need to support the diagnosis of anaphylaxis by objective markers. miRNAs are promising noncoding RNA species that may serve as serological biomarkers, but their use in diagnosing anaphylaxis has not been systematically studied to our knowledge. We aimed to comprehensively investigate serum biomarker profiles (proteins, lipids, and miRNAs) to support the diagnosis of anaphylaxis.Methods Adult patients admitted to the emergency room with a diagnosis of anaphylaxis (<3 hours) were included. Blood samples were taken upon emergency room arrival and 1 month later.Results Next-generation sequencing of 18 samples (6 patients with anaphylaxis in both acute and nonacute condition, for 12 total samples, and 6 healthy controls) identified hsa-miR-451a to be elevated during anaphylaxis, which was verified by quantitative real-time PCR in the remaining cohort. The random forest classifier enabled us to classify anaphylaxis with high accuracy using a composite model. We identified tryptase, 9α,11β-PGF2, apolipoprotein A1, and hsa-miR-451a as serological biomarkers of anaphylaxis. These predictors qualified as serological biomarkers individually but performed better in combination.Conclusion Unexpectedly, hsa-miR-451a was identified as the most relevant biomarker in our data set. We were also able to distinguish between patients with a history of anaphylaxis and healthy individuals with higher accuracy than any other available model. Future studies will need to verify miRNA biomarker utility in real-life clinical settings.Funding This work is funded by the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) as part of the clinical research unit (CRU339): Food Allergy and Tolerance (FOOD@) (project number 409525714) and a grant to MW (Wo541-16-2, project number 264921598), as well as by FOOD@ project numbers 428094283 and 428447634.